OTWARTE FORMY PRACY W GLOTTODYDAKTYCE – SPECYFIKA OCENIANIA W EDUKACJI SZKOLNEJ ORAZ W AKADEMICKIM KSZTAŁCENIU NAUCZYCIELI JĘZYKÓW OBCYCH - Peć, Beata (Neofilolog, 2020)
Open forms of work are now successfully used both in foreign language lessons and in academic education. Often, it may be difficult to assess the work of learners due to its specificity – that is, the summing and shaping of the assessment of the achievement of teaching objectives in school education and the effects of education in the didactics of the university. The question arises how to assess the work of learners during free work, while learners are working to attainment targets, working to weekly plans or doing project work. These issues will be subjected to theoretical analysis and discussed on the basis of my own empirical research in two areas of language teacher/foreign language education. On this basis conclusions will be formulated and research perspectives will be outlined with relation to school education and the academic education of foreign language teachers.